Finding our way home [large type] - Baumbich, Charlene Ann, 1945- (Baumbich, Charlene Ann, 1945- Snowglobe connections novel., 2012)
After ballet dancer Sasha Davis suffers a career-ending injury and returns home to Minnesota to recover and deal with her mother's death, she forms an unexpected bond with her live-in aide, Evelyn, who helps Sasha face life with a renewed purpose.